A Study on Effect of Asynchronous Control with Cttsin Micro grid System - Sung Lim, Hyun; Lee, Gun Ho; Ju Chae, Dong; Koo Cho, Sung; Ryu, In-Ho (International Journal of Engineering and Technology, 2018)
Background/Objectives: Â Recently, electrical consumption is increase every years. But expansion of power generation faced with environmental regulation. So, the government process 3020 policy of renewable energy and microgrid system.Methods/Statistical analysis: Microgrid system has Many DERs(Photovoltaic, Wind Power, Generator) and need to transfer uninterrupted control. So, this paper studies effect of asynchronous control with CTTS in microgrid system.Findings: To simulate effect of asynchronous control in mircogrid system, we consist CTTS modeling with EMTDC/PSCAD program. This program analyzes transient status of power system. CTTS operated synchronous conditions(Voltage, Frequency, Phase difference). First, we simulated reference simulation with same voltage, frequency and phase. Next, we experiment changing each condition. Then, we compared between reference simulation result and asynchronous simulation result. The result of maximum surge current can analyze effect of uninterrupted microgrid system.Improvements/Applications: This result can be adapted design microgrid safety operating process and improve safety standard of CTTS operation.Â Â Â